Strong positive cooperativity in binding to the A3T3 repeat by Hoechst 33258 derivatives attaching the quinoline units at the end of a branched linker. Issue 15 (1st August 2015) - Koda, Hironori; Brazier, John Alan; Onishi, Ippei; Sasaki, Shigeki
Graphical abstract: Abstract: Hoechst 33258 derivatives with additional interacting moieties attached at the ends of branched linkers were synthesized, and their DNA binding properties were investigated with regard to the A3T3 repeat by measuring fluorescence spectra. The binding property of the ligand was investigated by fluorescence titration, and the titration data were analyzed using the McGhee–von Hippel method. Ligand 6Q with the quinolin-6-yloxyacetyl group and Ligand IQ with isoquinolin-6-yloxyacetyl group at the ends of the branched linkers exhibit highly positive cooperativity for the DNA having 5 A3T3 sites with 3 base-insertions between them with sequence selectivity. The strategy developed in this study may be generally applicable for designing ligands for repetitive DNA sequences.